2022
DOI: 10.1007/s12519-022-00661-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of cerebrospinal fluid in pediatric myelin oligodendrocyte glycoprotein antibody-associated disease

Abstract: Background Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is an autoimmune demyelinating disorder of the central nervous system. Methods Extracted proteins from 34 cerebrospinal fluid (CSF) samples [patients with MOGAD (MOG group, n = 12); healthy controls (HC group, n = 12); patients with MOG seronegative and metagenomics next-generation sequencing-negative inflammatory neurological diseases (IND group, n = 10)] were process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…By comparing protein expression profiles between the MOG group and healthy controls, functional analysis revealed that the dysregulated proteins, including CTSF, were primarily involved in various biological processes such as complement and coagulation cascades, cell adhesion, axon guidance and glycosphingolipid production. However, the limited sample size in the study by Wang et al prevented further confirmation of these potential biomarkers [ 71 ], given that previously published research shows variance in prevalence between populations [ 72 ].…”
Section: Involvement Of Ctsf and Ctsw In Immune Response And Neurolog...mentioning
confidence: 99%
“…By comparing protein expression profiles between the MOG group and healthy controls, functional analysis revealed that the dysregulated proteins, including CTSF, were primarily involved in various biological processes such as complement and coagulation cascades, cell adhesion, axon guidance and glycosphingolipid production. However, the limited sample size in the study by Wang et al prevented further confirmation of these potential biomarkers [ 71 ], given that previously published research shows variance in prevalence between populations [ 72 ].…”
Section: Involvement Of Ctsf and Ctsw In Immune Response And Neurolog...mentioning
confidence: 99%